Математичне моделювання перехідних процесів у лінії Лехера в стані неробочого ходу - Чабан, Андрій Васильович; Левонюк, Віталій Романович; Дробот, Іван Михайлович; Герман, Андрій Фердинандович (НТУ "ХПІ", 2010)
У роботі, на основі узагальненого міждисциплінарного (інтердисциплінарного) методу математичного моделювання, який ґрунтується на модифікації інтегрального варіаційного принципу Гамільтона-Остроградського, запропоновано математичну модель двопровідної довгої лінії електропередач, що працює в неробочому стані. Представлено результати комп'ютерної симуляції перехідних процесів у вигляді рисунків, які аналізуються.

Purpose. The work proposed for the modeling of transients in Lehera line uses a modified Hamilton-Ostrogradskiy principle. The above approach makes it possible to avoid the decomposition of a single dynamic system that allows you to take into account some subtle hidden movements. This is true for systems with distributed parameters, which in the current work we are considering. Methodology. Based on our developed new interdisciplinary method of mathematical modeling of dynamic systems, based on the principle of modified Hamilton- Ostrogradskiy and expansion of the latter on the non-conservative dissipative systems, build mathematical model Lehera line. The model allows to analyze transient electromagnetic processes in power lines. Results. In this work the model used for the study of transients in the non-working condition Lehera line. Analyzing the results shows that our proposed approach and developed based on a mathematical model is appropriate, certifying physical principles regarding electrodynamics of wave processes in long power lines. Presented in 3D format, time-space distribution function of current and voltage that gives the most information about wave processes in Lehera line at non-working condition go. Originality. The originality of the paper is that the method of finding the boundary conditions of the third kind (Poincare conditions) taking into account all differential equations of electric power system, i.e. to find the boundary conditions at the end of the line involves all object equation. This approach enables the analysis of any electric systems. Practical value. Practical application is that the wave processes in lines affect the various kinds of electrical devices, proper investigation of wave processes is the theme of the present work
Mathematical model of electromagnetic processes in Lehera line at open-circuit operation
Keywords: принцип Гамільтона-Остроградського; рівняння Ейлера-Лагранжа; електроенергетична система; лінія електропередач; mathematical modeling; Hamilton-Ostrogradskiy principle; Euler-Lagrange equation; electric power system